The cost of sustainability in higher education: staff and student views of a campus food culture. Issue 2 (14th December 2017) - Shaw, Amy; Capetola, Teresa; Lawson, Justin T.; Henderson-Wilson, Claire; Murphy, Berni
Abstract : Purpose: This study aims to investigate the sustainability of the food culture at Deakin University and to determine what the barriers to increasing the sustainability of food on the Burwood campus may be. Design/methodology/approach: An online survey of staff and students from the Faculty of Health at the Burwood campus of Deakin University ( n = 697) was undertaken. The survey included questions relating to eating habits on campus, views on the current food culture, food security, food disposal, visions for the future and demographic information. In addition, a short paper-based survey was developed for the ten food outlets on campus. Findings: The results show that although sustainability considerations are important to staff and students, cost is the main issue and is a significant barrier to the development of a more sustainable food culture. It is also a significant barrier to staff and students making healthy choices when it comes to the purchase of food on campus. However, sustainable food initiatives such as community gardens could help alleviate this barrier and also contribute to improving student engagement. Research limitations/implications: The online survey was limited to the Faculty of Health, and, therefore, a potential bias exists towards individuals who may have an interest in health. This should be considered when interpreting the results. Originality/value: This research demonstrates that although cost may be a barrier to universities improving the sustainability of their food culture, there are other ways in which universities can create an environment that embraces sustainable food production to benefit both the environment and the university community.